Sociocultural context of exclusive breastfeeding in Africa: A narrative review - Amzat, Jimoh; Aminu, Kafayat; Matankari, Brisca; Ismail, Abbas; Almu, Bello; Kanmodi, Kehinde Kazeem (Health science reports, 2024)
Background and Aims Although exclusive breastfeeding (EBF) has many benefits, it is not commonly practiced in several countries as a result of context‐specific challenges. EBF practice is thus a global health discourse because over 200 million children suffer from malnutrition despite the abundance of human milk. The risk of starvation remains very high among African children with less than 40% of them exclusively breastfed. In Africa, the adoption or nonadherence to EBF is a sociocultural issue. Hence, this narrative review examined the sociocultural context of EBF in the region. Methods PubMed, Google Scholar, and Scopus were searched using keywords related to EBF and Africa. Relevant data from selected studies were synthesized narratively and reported using a structured narrative format. Results EBF is strongly rooted in every culture and is a culturally determined behavior. Some believe that colostrum is dirty and harmful to newborns and, thus, needs to be purified. Despite the belief that human milk is the best food for babies, mothers often complement human milk with other foods right from birth because of perceived lactation inadequacy. Most African mothers believe in prelacteal feeding to help cleanse the infant's gastrointestinal tract for digestion, quench thirst, flush the bladder and help the mother to rest after childbirth before breastfeeding (BF) is initiated. The role of significant others was equally found important in the decision and duration of BF. The availability of family support (especially from grandmothers and husbands) reportedly encouraged EBF in Africa. The duration and exclusivity of BF in Africa are negatively associated with demographic variables like young age, low level of education, being unmarried, low income, out of employment, and parity (first‐time mother). Conclusion While there have been some efforts and policies to improve EBF, it is important to consider context‐specific challenges and sociocultural factors. There is a need for more deliberate efforts to encourage mothers through the implementation of effective best practices concerning EBF in Africa.